2022
DOI: 10.3389/fped.2022.856159
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Models for Bronchopulmonary Dysplasia in Preterm Infants: A Systematic Review

Abstract: ObjectiveTo provide an overview and critical appraisal of prediction models for bronchopulmonary dysplasia (BPD) in preterm infants.MethodsWe searched PubMed, Embase, and the Cochrane Library to identify relevant studies (up to November 2021). We included studies that reported prediction model development and/or validation of BPD in preterm infants born at ≤32 weeks and/or ≤1,500 g birth weight. We extracted the data independently based on the CHecklist for critical Appraisal and data extraction for systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…Only infants with moderate or severe BPD were considered to have BPD; as a result, we anticipated that our findings would not differ remarkably from those reported in the current literature. In a sys-tematic review of BPD prediction models, oxygen dependency at a PMA of 36 weeks was the most frequently reported outcome [16]. Our findings are consistent with most of the studies mentioned in that review.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Only infants with moderate or severe BPD were considered to have BPD; as a result, we anticipated that our findings would not differ remarkably from those reported in the current literature. In a sys-tematic review of BPD prediction models, oxygen dependency at a PMA of 36 weeks was the most frequently reported outcome [16]. Our findings are consistent with most of the studies mentioned in that review.…”
Section: Discussionsupporting
confidence: 90%
“…Despite advances in neonatal and perinatal management, BPD remains a major cause of morbidity and mortality in preterm infants. It is essential to further Prediction Model for Bronchopulmonary Dysplasia develop preventive measures and treatment approaches in the early days of life when airway injuries are still reversible [16]. In addition, earlier prediction of BPD may help individualize neonatal care and optimize precision medicine.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the use of a competing risks methodology could provide a more unbiased estimate of the probability of BPD and the HR associated with each of the covariates considered, which may lead to a better predictive ability. On the other hand, all variables finally included in the models have been previously described in the literature as risk factors for the disease and are biologically plausible ( 9 ). In this respect, we would like to highlight the simplicity of our models, which consist of a limited number of objective clinical variables, recorded at bedside during the first days of life.…”
Section: Discussionmentioning
confidence: 99%
“…Good-quality predictive models for BPD aim to establish an individual risk of BPD, helping clinicians to identify high-risk patients and individualize care, and hopefully enabling more effective preventive strategies. While a plethora of predictive models have been developed in recent decades ( 9 ), none are fully incorporated into routine clinical practice ( 5 , 10 ) and all suffer from a high risk of bias ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…In their analysis of 26 studies, Onland et al ( 10 ) identified that predictive models for BPD lacked calibration. Peng et al ( 18 ) reported on 18 models for predicting BPD or death in preterm born at ≤32 weeks' gestation, most of which had many methodological shortcomings and lacked calibration assessment. To address these issues, our study included validation cohorts and calibration to enhance the predictive value of our model.…”
Section: Discussionmentioning
confidence: 99%